H01 Significant biological and clinical change detected over 1 year in premanifest and early stage Huntington's disease in the TRACK-HD study. (16th November 2010) - Tabrizi, S J; Dürr, A; Roos, R A C; Leavitt, B R; Jones, R; Landwehrmeyer, G B; Johnson, H; Hicks, S L; Kennard, C; Reilmann, R; Craufurd, D; Rosas, H D; et al.
Abstract : Background/aims: TRACK-HD is a multinational prospective, observational study of Huntington's disease (HD) that aims to examine longitudinal change in premanifest carriers of the mutant HTT gene and subjects with early stage disease (Tabrizi et al. Lancet Neurology 2009). New data from the first follow-up assessment are reported here, and build on previous findings from baseline 3T MRI and novel clinical, cognitive, quantitative motor, oculomotor and neuropsychiatric assessments. Of 366 subjects enrolled at baseline, 345 (115 controls, 116 premanifest (preHD) and 114 early HD) completed 12 months of follow-up. Statistical analysis was performed to assess annualised change in all modalities. Methods/techniques: Annualised rates of global and regional atrophy were higher in both the pre- and early HD groups than in controls (p≤0.007). Whole brain atrophy rates were 0.3%, 0.5% and 0.9%, and caudate atrophy rates 0.6%, 2.0% and 3.5%, in controls, pre and early HD, respectively, over 1 year. Whole brain image analysis techniques also revealed striking cortical and subcortical grey and white matter atrophy over just 1 year even in subjects furthest from predicted disease onset. Quantitative imaging showed significant associations with disease burden and total functional capacity, a widely used clinical measure of disease severity. Cognitive deterioration was detectable in both HD groups. However, rates of decline in cognitive, quantitative motor and oculomotor tasks were greater after onset of motor signs. Results/outcome: HD is characterised by a long premanifest state, slow progression and a disease course of around 20 years. After 1 year, we have identified robust change in a range of measures across modalities in both premanifest and early stage HD. Quantitative imaging showed the greatest differentiation across the spectrum of the disease and a number of functional measures of decline were sensitive in early HD with cognitive impairment also detectable in the pre-HD group. Conclusions: TRACK-HD is the first multi-site study to report whole brain, regional and subcortical atrophy in premanifest subjects many years from predicted disease onset using 3T MR imaging; and demonstrates the feasibility of obtaining quantifiable endpoints which show robust change over just 1 year thus showing potential as endpoints for future therapeutic trials.